Artificial seawater for seaweed culture - Kaladharan, P (Indian Journal of Fisheries, 2011)
Artificial seawater prepared with simplified recipes was found suitable formaintaining seaweeds of commercial importance under laboratory conditions. Thesuitability of this artificial seawater formulation studied by gain or loss of wetweight of seaweeds incubated, showed 15.5% increase in specific growth rate inthe case of Gracilaria corticata and 18% increase in the case of Ulva lactuca.However, Gracilaria edulis showed 14% decrease over the control. Physicochemicalcharacteristics of artificial seawater were compared with these of naturalseawater.